Hille and Nehari Type Oscillation Criteria for Conformable Fractional Differential Equations - T. Gayathri; M. Sathish Kumar; Sadhasivam, V. (Iraqi Journal of Science, 2021)
In this paper, we develop the Hille and Nehari Type criteria for the oscillation of all solutions to the Fractional Differential Equations involving Conformable fractional derivative. Some new oscillatory criteria are obtained by using the Riccati transformations and comparison technique. We show the validity and effectiveness of our results by providing various examples.